Le “nuove guerre” della globalizzazione - Greblo, Edoardo (Philosophy Kitchen - Rivista di filosofia contemporanea, 2015)
In speeches on global security is recurring the idea that the «new wars» are the expression of a type of organized violence that differs substantially from armed conflicts typical of previous eras. According to several authors, the factors which could bring in an overall perspective this diversified set of phenomena is globalization: the «new wars» are, namely, an integral part of the transformation of modernity that are changing the scale of the organization of human society.